Capim Xaraés inoculado com bactérias diazotróficas associativas - Bosa, Christiane Kamila (2014)
The objective was to evaluate the inoculation of associative diazotrophs bacteria with Brachiaria brizantha cv. Xaraés in the first cultivation in the Cerrado Oxisol. The experiment was conducted in a greenhouse at the University Campus RondonópolisMT. The experimental design was completely randomized factorial consisting of 7x3, corresponding to seven treatments: three strains of associative diazotrophs bacteria (MTAz8, MTH2 and Y2), a combination of strains MTAz8 and MTH2, nitrogen fertilization (with nitrogen, phosphorus and potassium), witness (free of inoculation and nitrogen, but with phosphorus and potassium) here called control (no N) and absolute control (without inoculation and fertilization), and three cuts(30, 60 and 90 days) in five replications. The inoculation was performed by inserting an aliquot of 5 ml of the bacterial broth containing 108 ml-1 cells in the soil near the root zone of each plant. After each cut, was made the re-inoculation of bacteria, as well as nitrogen and potassium fertilization. There was a significant interaction effect between inoculation and cuts for most variables, the bacteria that stood out were the strains Y2 and MTH2, with increases in total dry mass of the aerial part of (8,66 and 7,27%) when compared to control without inoculation and nitrogen, even not among them. The higher nitrogen accumulation was observed in N fertilization growing over the cuts, while the inoculated treatments and control (no N) did not differ, and decreased over the cuts. Therefore, it is concluded that the nutritional characteristics, crude protein and nitrogen concentration and accumulation in Xaraés grass declined with cuts were carried to the sixty and ninety days of cultivation. The dry matter production of Xaraés grass inoculated showed an average increase of 11,32% compared treatments inoculated control without nitrogen and inoculation. The bacterial strains studied showed low competition with the microorganisms in the soil and among the bacteria studied the Y2 and MTH2 strains showed potential for FBN in association with the xaraés grass at first crop in the Cerrado Oxisol.